MAPPING POLITICAL IDEOLOGY IN SOCIAL MEDIA NARRATIVES: A CRITICAL DISCOURSE ANALYSIS OF X (TWITTER) POSTS ON PRESIDENT PRABOWO USING VAN DIJK'S MODEL - Cindy Salsabila Ginting (Universitas Negeri Islam Sumatera Utara, 2025)
This study examines how political ideology and leadership are constructed and contested in X (formerly Twitter) posts about President Prabowo's international activities using Teun A. van Dijk's Critical Discourse Analysis model. Drawing on a qualitative corpus of posts from the president's official account, news media, and citizen commentators, the research analyses macro structures (dominant themes), superstructures (narrative and evaluative schemas), and micro structures (lexical, stylistic, and visual features) related to foreign visits. Purposive sampling and close textual analysis reveal three macro themes: heroic diplomacy and strategic partnership, which dominate official and media posts, and contested leadership, which is prominent in citizen commentary. The findings show that institutional discourses normalise an image of energetic, globally engaged leadership, whereas citizen posts use irony, colloquial language, and satire to reframe the same events as objects of critique, questioning priorities, competence, and the link between international visibility and domestic legitimacy. The study concludes that X functions as a hybrid arena where political legitimacy is co‑constructed by institutional actors and ordinary users in Indonesia's digital public sphere.